The effect of tofu liquid waste on mortality and histopathology of goldfish (Cyprinus carpio) kidney as a biology alternative material concept for senior high school X grade - Ria Mayasari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
Liquid waste of tofu is a liquid-byproduct of tofu production proces which is known as "whey". Most of the "whey" can not be utilized. Thus, the liquid waste of tofu that flowed directly into the river, without any extent process to neutralize will cause the death fish. The effect of tofu liquid waste can be observed throughout the histopathological observation (especially the kidneys). This study aims to determine the effect of tofu liquid waste on mortality and histopathology of goldfish kidney. This study employed an experimental method using goldfish with the size of 8-12cm. The data collection was started by preliminary test in which the liquid concentration were of 0 ml/L, 0,1 ml/L, 1 ml/L, 10 ml/L, and 100 ml/L, which then the real tests were conducted by using RAND method to obtain the concentration of 0 ml/L, 32 ml/L, 56 ml/L, 75 ml/L, and 87 ml/L. The LC50 goldfish observational data have been analyzed by using Probit Model Finney program "Quant"; meanwhile, the goldfish kidney taken per concentration unit as samples for histopathological observation. The results showed that the tofu liquid waste gave significant impact on mortality and the occurrence of goldfish kidney damage (histopathology), such as hemorrhage, congestion, and necrosis. Based on the data, this study can be recommended as enrichment of biology alternative material for X grade of senior high school at KD 3.10 i.e. to analyze the data of environmental changes and the impact of such changes for life.